Islam & Life: A Multifaceted Approach To Values And Practices - St. Maemunah; Andi Anderus; Hamzah Harun (Manunggal Halim Jaya, 2026)
This research aimed to analyze the values and practices of Islam through a multi-aspect approach, focusing on how Islamic teachings influenced various dimensions of human life, such as theology, social, political, and cultural aspects. The methods used in this research were literature review and qualitative analysis of the Qur'an, Hadith, classical and contemporary literature regarding Islamic values and practices. The findings indicated that Islam, as a religion and belief system with universal principles and values, has had a significant influence and development, impacting various cultural, social, and political contexts in society. The implications of this research highlight the importance of a deeper understanding of how Islam interacts with all aspects of life, as well as the need for a more inclusive and adaptive approach to practicing Islamic teachings in the era of globalization. This research also provides insights into the role of Islam in shaping social, cultural, and political policies that promote justice.